2019
DOI: 10.1128/aac.01909-18
|View full text |Cite
|
Sign up to set email alerts
|

Decyl Gallate as a Possible Inhibitor of N-Glycosylation Process in Paracoccidioides lutzii

Abstract: The available antifungal therapeutic arsenal is limited. The search for alternative drugs with fewer side effects and new targets remains a major challenge. Decyl gallate (G14) is a derivative of gallic acid with a range of biological activities and broad-spectrum antifungal activity. Previously, our group demonstrated the promising anti-Paracoccidioides activity of G14. In this work, to evaluate the antifungal characteristics of G14 for Paracoccidioides lutzii, a chemical-genetic interaction analysis was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Glucose-regulating protein 78 (GRP78) plays an important regulatory role in UPR . Under normal conditions when UPR is not activated, inactive GRP78 binds and forms a stable complex with activating transcription factor 6 (ATF6), protein kinase RNA-like endoplasmic reticulum kinase (PERK), and inositol-requiring enzyme 1 (IRE1)three ER transmembrane proteins that act as intracellular receptors for the UPR signal transduction pathway. , The accumulation of misfolded or unfolded proteins in the ER leads to dissociation of these three sensor proteins from GRP78; this leads to increased expression of GRP78, which, in turn, triggers the three parallel signaling pathways of UPR to protect the cell . Therefore, GRP78 can be employed as a marker to assess UPR activation in cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose-regulating protein 78 (GRP78) plays an important regulatory role in UPR . Under normal conditions when UPR is not activated, inactive GRP78 binds and forms a stable complex with activating transcription factor 6 (ATF6), protein kinase RNA-like endoplasmic reticulum kinase (PERK), and inositol-requiring enzyme 1 (IRE1)three ER transmembrane proteins that act as intracellular receptors for the UPR signal transduction pathway. , The accumulation of misfolded or unfolded proteins in the ER leads to dissociation of these three sensor proteins from GRP78; this leads to increased expression of GRP78, which, in turn, triggers the three parallel signaling pathways of UPR to protect the cell . Therefore, GRP78 can be employed as a marker to assess UPR activation in cells.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 The accumulation of misfolded or unfolded proteins in the ER leads to dissociation of these three sensor proteins from GRP78; this leads to increased expression of GRP78, which, in turn, triggers the three parallel signaling pathways of UPR to protect the cell. 58 Therefore, GRP78 can be employed as a marker to assess UPR activation in cells. Adsorption studies suggested the adsorption of RPN1 onto NPs in THP-1 cells (Figure 4C).…”
Section: Genetic Information Processing Pathway Protein Adsorption An...mentioning
confidence: 99%
“…For glycosylated protein analysis, yeast cells were washed after the peptide treatments described above and stained with 100 µg/mL of ConA-Alexa Fluor 488 at 37 • C, 150 rpm for 1 h. Fungal cells were washed, resuspended in PBS, and analyzed using a BD FAC-SCanto flow cytometer. The mean fluorescence intensity of 10,000 cells in the fluorescein isothiocyanate channels was determined [37].…”
Section: Cell Wall Modifications Mediated By Exposure Of Fungi To Pep...mentioning
confidence: 99%
“…Potential compounds act as growth inhibitors against Paracoccidioides spp. in low concentrations ( Table S1 ), such as alkyl gallates (0.004–16 µg/mL), an N-Glycosylation inhibitor [ 38 , 39 ]; the thiosemicarbazone lapachol, which acts on the plasma membrane (0.01–0.1 µM) [ 40 ]; azasterol analogs (0.5–10 µM) [ 41 ] and hydrazone derivatives (0.1–5 µM) [ 42 ], as inhibitors of ergosterol biosynthesis. These compounds are less potent when compared to azole derivatives, such as itraconazole with a 0.003–0.05 µM MIC [ 33 ]; luliconazole, a topical antifungal repositioned against Paracoccidioides spp.…”
Section: New Anti- Paracoccidioides Compounds: mentioning
confidence: 99%